THE EVOLUTION OF UNDERGROUND ARCHITECTURE IN THE TERRITORY OF CONTEMPORARY UKRAINE: FROM THE PALEOLITHIC ERA TO THE LATE 20TH CENTURY - Hubanishchev Оleh (Theory and practice of design, 2025)
The article is devoted to a comprehensive analysis of the periods and specific features of the formation of underground structures on the territory of Ukraine — from prehistoric times to the mid-20th century. Attention is paid to identifying the preconditions for the emergence and use of such facilities, which makes it possible to determine the stages of evolution of underground construction depending on natural-geographical and social factors. The article briefly describes and illustrates underground construction sites in Ukraine — from Paleolithic caves to 20th-century bunkers. Based on information from historical sources, archaeological data, and architectural analysis, the characteristic features of the planning and spatial structure of underground objects are defined. Purpose. A comprehensive analysis of the evolution of underground structures on the territory of modern Ukraine from the Paleolithic era to the second half of the 20th century, focusing on identifying the preconditions for their emergence, functional and spatial characteristics, and patterns of development. Methodology. The study is based on the analysis of historical sources, archaeological data, graphic materials (plans, sections, photographs), and design standards for underground facilities, as well as on the methods and approaches most common in domestic and international research practices of architectural heritage, mining technologies, and underground construction. Research methods. A systemic approach to the study of the object as an integral part of Ukraine’s historical and cultural heritage, with chronological and typological analysis of the evolution of underground structures in the context of socio-cultural, natural, and technological factors. Results. The study examines the role of underground structures in meeting society’s vital needs (from sacred and residential to defensive and industrial functions); the main factors influencing their planning and spatial structure (natural formations, extraction technologies, social conditions); and typological characteristics (seven stages with examples of objects). The research reveals patterns of evolution from isolated caves to multifunctional complexes and urban systems. Particular attention is given to more than 20 underground sites in Ukraine, including Crimean cave towns, monasteries, shelters, and 20th-century bunkers, with a proposed classification table. Scientific novelty. The scientific novelty lies in the comprehensive periodization of the evolution of underground construction in Ukraine, which is lacking in existing fragmented studies. The work emphasizes the integration of underground structures into the urban environment and their transformation from mono-functional to multi-functional complexes. The findings can supplement the existing classification system of architectural heritage and be applied in further research and in the practical revitalization of such sites. Practical relevance. The obtained results can be implemented in the processes of museification and revitalization of underground monuments to promote tourism and cultural development. Drawing additional attention to the historical development of underground spaces contributes to the advancement of a relevant architectural vector in contemporary Ukraine.